2016 International Conference on Industrial Informatics and Computer Systems (CIICS) 2016
DOI: 10.1109/iccsii.2016.7462419
|View full text |Cite
|
Sign up to set email alerts
|

OCR based feature extraction and template matching algorithms for Qatari number plate

Abstract: There are several algorithms and methods that could be applied to perform the character recognition stage of an automatic number plate recognition system; however, the constraints of having a high recognition rate and real-time processing should be taken into consideration. In this paper four algorithms applied to Qatari number plates are presented and compared. The proposed algorithms are based on feature extraction (vector crossing, zoning, combined zoning and vector crossing) and template matching technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Hamming distance [64], Euclidean distance [63,85], Cosines and scalar product [86], and Normalized Cross-Correlation (NCC) [87] were used to find the similarity between templates in many Arabic OCR approaches. Farhat et al [88] segmented the image of the Qatari Plate into characters, then each character image is divided into four zones, and finally, template matching is used to recognize the character label. Nosseir et al [44] extracted SURF features from the Egyptian ID Cards, then template matching is used to classify the characters.…”
Section: Template Matchingmentioning
confidence: 99%
“…Hamming distance [64], Euclidean distance [63,85], Cosines and scalar product [86], and Normalized Cross-Correlation (NCC) [87] were used to find the similarity between templates in many Arabic OCR approaches. Farhat et al [88] segmented the image of the Qatari Plate into characters, then each character image is divided into four zones, and finally, template matching is used to recognize the character label. Nosseir et al [44] extracted SURF features from the Egyptian ID Cards, then template matching is used to classify the characters.…”
Section: Template Matchingmentioning
confidence: 99%
“…The algorithm [12] Discussed extract the lines and curves which the alphabet is made is using the feature recognition based OCR. In [13] four different OCR techniques namely vectors crossing, Zoning, combination of vector crossing and Zoning and Template matching are proposed. The results obtained from these four methods are compared and it is shown that template matching technique yields better accuracy of 99.5% with an average time of 1.95 m sec per each character.…”
Section: Literature Surveymentioning
confidence: 99%
“…Then, by formulating the assignment problem as a binary quadratic problem, which allows considering pairwise relations as well as local properties.In this paper, for character recognition following steps are followed-1) Find out Character 2) Choose the Character 3) For using the first template size of image is rescale 4) Comparison with Template 5) Record the maximum match as a indentified character. Ali Farhat et al [4] proposed four algorithms applied to Qatari number plates. The four algorithms are based on feature extraction (vector crossing, zoning, combined zoning, and vector crossing) and template matching techniques.…”
Section: Literature Survey a Suman Avdhesh Yadav Proposed A Systmentioning
confidence: 99%